2009
DOI: 10.1021/la902341w
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Scale Preparation of Surfactant-Free, Carboxylic Acid Groups Functionalized, Individual Single-Walled Carbon Nanotubes in Aqueous Solution

Abstract: We report a simple method to prepare individual electric arc-produced single-walled carbon nanotubes (SWNTs) in aqueous solution on a large scale through three steps of processing: refluxing in concentrated HNO(3), low speed centrifugation, and high speed centrifugation. The bulk production (10 g of starting SWNTs) results in a concentration of 0.2 mg/mL individual SWNTs stably dispersed in DI-H(2)O without any external protection. The atomic force microscopy images show that the aqueous dispersion contained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
(46 reference statements)
0
21
0
Order By: Relevance
“…The RBM of the as‐purified SWCNTs shows multiple peaks (spectrum I in Figure 5a), corresponding to a wide diameter distribution of SWCNTs, which is consistent with the HRTEM results in Figure S1. It is worth noting that the diameter of the SWCNTs is much larger than that of two widely‐used commercial SWCNTs: HiPCO (with diameter of 0.7–1.3 nm) and arc‐discharge SWCNTs (with mean diameter of 1.38 nm) 42. After oleum and nitric acid treatment, the intensity of the RBM peak is dramatically decreased and the G band is blue shifted from 1589 to 1599 cm −1 , due to the strong p‐type chemical doping by sulfuric and nitric acids 43–45.…”
Section: Resultsmentioning
confidence: 97%
“…The RBM of the as‐purified SWCNTs shows multiple peaks (spectrum I in Figure 5a), corresponding to a wide diameter distribution of SWCNTs, which is consistent with the HRTEM results in Figure S1. It is worth noting that the diameter of the SWCNTs is much larger than that of two widely‐used commercial SWCNTs: HiPCO (with diameter of 0.7–1.3 nm) and arc‐discharge SWCNTs (with mean diameter of 1.38 nm) 42. After oleum and nitric acid treatment, the intensity of the RBM peak is dramatically decreased and the G band is blue shifted from 1589 to 1599 cm −1 , due to the strong p‐type chemical doping by sulfuric and nitric acids 43–45.…”
Section: Resultsmentioning
confidence: 97%
“…where D is the diameter of the film ($4 cm); t is the thickness of the film; q is the density of the graphene-based material (assumed as 2.2 g/cm 3 -the density of bulk graphite); V is the volume of the dispersion and C is the concentration of graphene in dispersion (mg/ ml) [19]. This equation was previously used by Yu et al [19] for calculation of the thickness of carbon nanotube films; here it was adapted for graphene-based films. Accordingly, it was found that the thickness values of the graphene-based thin films range from 43 to 86 nm depending on the volume and the concentration of the dispersions used.…”
Section: Thin Film Preparationmentioning
confidence: 99%
“…This can also be determined by the zeta-potential measurement of SWNTs in solvent. If ionic surfactant is used or absolute value of measured zeta-potential is much larger than zero, the dispersion is stabilized by electrostatic repulsion; by contrast, static repulsion dominates for nonionic surfactant and relatively small zeta-potential [93,[117][118][119]. Moreover, zeta-potential measurement can also be applied to determine the dispersion effect of SWNTs; usually, when the absolute value of zeta-potential ζ > 15 mV, the CNT is well dispersed in solvents and expected to be stable.…”
Section: Surfactants and Aqueous Solutionsmentioning
confidence: 99%